Kebebasan Berpendapat di Era Digital: Kajian Yuridis tentang Pembatasan Berdasarkan UU ITE dan HAM - Siregar, Dahris (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Digital technology has revolutionized Indonesia's freedom of speech, however, the Electronic Information and Transaction Law (ITE Law) calls into question excessive restrictions on human rights. This study aims to investigate whether the ITE Law's limitations on free expression are acceptable and how the government enforces them. Utilizing a normative juridical approach, this paper thoroughly investigates the ITE Law's provisions, especially paragraphs 27(3) on defamation and 28(2) on hate speech, and evaluates how law enforcement procedures implement them. The study's findings demonstrate that the ITE Law's provisions have serious flaws in terms of discriminatory application, proportionality of penalties, and norm clarity. The ITE Law satisfies the formal legality requirements, but it falls short of the legal clarity and proportionality standards demanded by international law, according to the analysis conducted using the framework of the three elements of human rights restriction (legality, legitimacy of purpose, and proportionality). This analysis comes to the conclusion that the ITE Law's implementation has significantly reduced online freedom of speech, with a pattern of law enforcement that tends to criminalize criticism of the government and public discussion of controversial issues. Studies comparing Indonesia's internet rules to those of democratic nations reveal that the former are comparatively less proportional and more restrictive.